Translanguaging as Everyday Practice (Multilingual Education, 2018)
This volume offers empirically grounded perspectives on translanguaging as a locally situated, interactional accomplishment of practical action, and its significance within different domains of social life-school, education, diasporic families and communities, workplaces, urban linguistic landscapes, advertising practices and mental health centres - focusing on case studies from different countries and continents. The 14 chapters contribute to the understanding of translanguaging as a communicative and discursive practice, which is relationally constructed and strategically deployed by individuals during everyday encounters with language and cultural diversity. The contributions testify to translanguaging as an interdisciplinary and critical research paradigm by assembling scholars working on translanguaging from different perspectives, and a wide range of social, cultural, and geographical contexts. This volume contributes to the further development of new theoretical and analytical tools for the investigation of translanguaging as everyday practice, and how and why language practices are constructed, negotiated, opposed or subverted by social actors.